Drug-induced antisynthetase syndrome. - Thickett, D. R. (BMJ Group, 1997)
We present a case of antisynthetase syndrome whose predominant feature was fibrosing alveolitis and which may have been drug-induced. This responded well to steroids and cyclophosphamide.